Redefining Quantum Dot Synthesis with Additive-Manufactured Microfluidics—A Review - Faisal bin Nasser Sarbaland; Masashi Kobayashi; Daiki Tanaka; Risa Fujita; Masahiro Furuya (J, 2025)
Quantum dots with sizes between 1 and 100 nm possess unique optical and electronic properties, making them valuable in energy, bioimaging, and optoelectronics fields. While traditional synthesis methods offer control over QD properties, they face challenges in scalability and reproducibility. Integrating microfluidics addresses these issues, providing precise control and high-throughput capabilities. This review highlights the transition from PDMS-based devices to additive-manufactured microfluidics, emphasizing their ability to overcome limitations in traditional methods. These advancements smooth the way for scalable, cost-effective, and sustainable QD production with enhanced application potential.